Psychiatric and Cognitive Aspects of Phenylketonuria: The Limitations of Diet and Promise of New Treatments - Ashe, Killian; Kelso, Wendy; Farrand, Sarah; Panetta, Julie; Fazio, Tim; De Jong, Gerard; Walterfang, Mark (Frontiers in Psychiatry, 2019)
Phenynketonuria (PKU) is a recessive disorder of phenylalanine metabolism due to mutations in the gene for phenylalanine hydroxylase (PAH). Reduced PAH activity results in significant hyperphenylalaninemia, which results in alterations to cerebral myelin and protein synthesis, as well as reduced levels of serotonin, dopamine and noradrenaline in the brain. When untreated, brain development is grossly disrupted and significant intellectual impairment and behavioural disturbance occur; however the advent of neonatal heelprick screening has allowed for diagnosis at birth, and the institution of a Phe-restricted diet. Dietary treatment, particularly when maintained across neurodevelopment and well into adulthood, has resulted in markedly improved outcomes at a cognitive and psychiatric level for PKU sufferers; however, few individuals can maintain full dietary control life-long, and even with good control, an elevated risk remains of – in particular - mood, anxiety and attentional disorders across the lifespan. Increasingly, dietary recommendations focus on maintaining continuous dietary treatment lifelong to optimise psychiatric and cognitive outcomes, although the “price” of long-term protein restricted diets on brain function remain unknown. Whilst psychiatric illness is very common in adult PKU populations, very little data exists to guide clinicians on optimal treatment. The advent of new treatments that do not require restrictive dietary management hold the promise of allowing patients a relatively normal diet alongside optimised mental health and cognitive functioning.